Trend Penyakit Demam Berdarah Dengue (DBD) di Sulawesi Tenggara Berbasis Ukuran Epidemiologi - Irma Irma; Swaidatul Masluhiya AF (Prodi Kesehatan Masyarakat Fakultas Kesehatan Masyarakat UIN Sumatera Utara, 2021)
Until now, Dengue Hemorrhagic Fever (DHF) is still a public health problem whose number of sufferers continues to increase from year to year and its spread is increasingly widespread. DHF cases are also still endemic and continue to spread in several districts / cities in Southeast Sulawesi Province. This research is a descriptive qualitative research with a population and the sample used is all data on DHF cases from the Southeast Sulawesi Provincial Health Office from 2015 to 2019 as many as 7142 cases. The data that has been collected is then analyzed with the help of the SPSS program to describe the trend of DHF cases based on epidemiological measurements. The results of this study indicate that trend of DHF cases in Southeast Sulawesi based on prevalence rates, Isidence Rate (IR) and Case Fatality Rate (CFR) in the last 5 years from 2015 to 2019 has fluctuated. The trend of DHF cases in Southeast Sulawesi peaked in 2016 year with a prevalence of 0.122% and an IR of 122.3 per 100,000 population while the CFR rate peaked in 2017 year at 1.01%. Keywords: CFR, DHF, epidemiological, IR, prevalence, trend